2017
DOI: 10.15294/dp.v12i1.10583
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Technology Acceptance Model in Understanding of Students Behavior Intention in Use of Sikadu

Abstract: The research aims to know the perception of students of ease use of Sikadu, the perception of students of usefulness use of Sikadu, and the impact of students' perception of ease and usefulness of Sikadu. The approach of this research used quantitative research with descriptive analysis. Sample was students of Faculty of Economics, class of 2015 and 2016. The results of research indicates that students' perception of the menu and display existing is easy to use in lecture activities up to the utilization of ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…In this regard, in the fi eld of education, the perceived usefulness and perceived ease of use constructs have long been studied and found to be feasible to determine the acceptance of using e-learning and mobile learning (Cheon et al, 2012;Park, 2009;Park et al, 2012;Widhiastuti & Yulianto, 2017). Many studies have consistently reported that both perceived usefulness and perceived ease of use are associated with perceived acceptance, whereas perceived enjoyment is found to be an important antecedent of perceived ease of use (Venkatesh & Davis, 2000).…”
Section: Finding and Discussionmentioning
confidence: 99%
“…In this regard, in the fi eld of education, the perceived usefulness and perceived ease of use constructs have long been studied and found to be feasible to determine the acceptance of using e-learning and mobile learning (Cheon et al, 2012;Park, 2009;Park et al, 2012;Widhiastuti & Yulianto, 2017). Many studies have consistently reported that both perceived usefulness and perceived ease of use are associated with perceived acceptance, whereas perceived enjoyment is found to be an important antecedent of perceived ease of use (Venkatesh & Davis, 2000).…”
Section: Finding and Discussionmentioning
confidence: 99%
“…Kelayakan penerimaan pembelajaran menggunakan e-learning dan mobile learning dapat diukur dari sejauh mana manfaat dan kemudahan dapat dirasakan oleh mahasiswa (Park et al, 2012;Widhiastuti & Yulianto, 2017). Sudah banyak laporan penelitian yang juga menyebutkan bahwa kesiapan dosen dalam mengelola pembelajaran online menggunakan ragam program aplikasi, konferensi virtual, video pembelajaran, e-modul, dan sebagainya akan menguatkan persepsi mahasiswa bahwa pembelajaran secara online akan sangat baik digunakan untuk membantu proses pembelajaran dan memberikan dorongan motivasi kepada mahasiswa bahwa pembelajaran online adalah pembelajaran yang menyenangkan serta mudah digunakan.…”
Section: Uji Hipotesis Mayor (H4)unclassified
“…The UTAUT and UTAUT 2 models are the underlie formation of strong relationship between behavior intention and user behavior. Previous research has stated that behavioral intentions affect to user behavior (Lin & Lai, 2019;Batoro, 2020;Purwanto & Loisa, 2020;Widhiastuti & Yulianto, 2017;Tak & Panwar, 2017). While other findings stated that behavioral intentions have succeeded becoming a mediator that connects the UTAUT 2 construct to user behavior (Gupta, 2018).…”
Section: Introductionmentioning
confidence: 98%